Rhyme and Alliteration in Translation - Kitanovska-Kimovska Sonja & Popovska Solzica (University “St. Kliment Ohridski“, Faculty of Education - Bitola, 2017)
A number of translation theorists have stated that translators’ primаry role is to convey the original text’s style and the esthetic effects it has on the reader. The role of literary translation is to recreate the artistic elements of the original in another language so that the readers of the translation are inspired, excited and esthetically entertained as the readers of the original are. In view of these considerations, rhyme and alliteration are important features of literary style, particularly poetry, and as such should be preserved in translation. However, due to the inherent differences between languages and between their phonemic and lexical systems, in particular, this can be a serious challenge for the literary translator. The purpose of this paper is to establish to what extent the original text’s rhyme and alliteration are preserved in translation. An analysis is made of 2 Shakespeare’s plays and 2 translations into Macedonian of each of these plays. The analysis is mainly qualitative where translation solutions are discussed in light of the artistic effects rhyme and alliteration have in the original. Quantitative analysis is also provided as an indication of the overall result of the translations. As one translation of each of the 2 texts is made from the original English source, whereas the other one is made from a text that is translation itself, the paper also provides insights into the differences between direct and indirect translation.
Keywords: translating style, rhyme, alliteration, Shakespeare, indirect translation